Longman dictionary of common errors - Heaton, J. B. (Longman, 1987)
*Over 2500 alphabetical entries, with language notes giving clear explanations of the problems underling each error *Authentic example sentences taken from the British National Corpus showing correct use in context *30 special language features focusing on key problem areas *Illustrations to aid comprehension and reinforce meaning *Comprehensive cross-references help you locate entries easily *Glossary of all grammatical terms used in the entries